CPPD—differential diagnostics and differential therapeutic challenges - Maria L. Voulgari; Herbert Kellner (Exploration of Musculoskeletal Diseases, 2024)
Calcium pyrophosphate deposition disease (CPPD), characterized by the presence of calcium pyrophosphate crystals in and around joints, poses diagnostic and therapeutic challenges in rheumatology. This review provides a comprehensive overview of CPPD, focusing on its diagnosis, differential diagnosis, therapeutic challenges, and monitoring, with insights into the association between CPPD and cardiovascular risk. Diagnostics in CPPD rely on identifying CPP crystals in synovial fluid or joint tissues, with imaging modalities such as ultrasound and conventional radiography emerging as valuable tools. The 2023 American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) classification criteria prioritize imaging evidence of CPP crystal deposition and recurrent episodes of acute inflammatory arthritis, aiding in standardized diagnosis. Differential diagnosis includes distinguishing CPPD from gout, osteoarthritis, rheumatoid arthritis, basic calcium phosphate deposition disease, and other inflammatory arthropathies. Therapeutic challenges in CPPD management revolve around symptomatic relief, with no targeted therapy to influence CPP deposition currently available. Management strategies include symptom-directed treatments like NSAIDs, steroids and colchicine. IL-6 inhibition with tocilizumab shows promise for refractory cases. Monitoring CPPD involves assessing joint symptoms, inflammation, and cardiovascular risk factors, with regular clinical evaluation. In conclusion, CPPD presents a complex challenge in rheumatology, requiring a nuanced approach to diagnosis and management. Ongoing research is needed to deepen our understanding of CPPD mechanisms and explore novel therapeutic avenues.